Revision of Goniocolletes and seven Australian subgenera of Leioproctus (Hymenoptera: Apoidea: Colletidae), and description of new taxa - Maynard, Glynn Vivian (Zootaxa, 2013)
This paper provides a revision of Goniocolletes Cockerell, and of Australian subgenera of Leioproctus Smith (Hymenoptera: Colletidae: Paracolletini) with three submarginal cells. Seven subgenera were revised: Leioproctus s.str., L. (Ceratocolletes) Michener, L. (Cladocerapis) Cockerell, L. (Excolletes) Michener, L. (Lamprocolletes) Smith, L. (Odontocolletes) Maynard, and L. (Protomorpha) Rayment, and seven new subgenera are herein described: L. (Alokocolletes) subgen.n., L. (Charicolletes) subgen.n., L. (Exleycolletes) subgen.n., L. (Fragocolletes) subgen.n., L. (Hadrocolletes) subgen.n., L. (Minycolletes) subgen.n. and L. (Zosterocolletes) subgen.n. Seven new species of Goniocolletes (Goinocolletes anthedonus sp.n.; Goniocolletes badius sp.n.; Goniocolletes ciliatus sp.n.; Goniocolletes comatus sp.n.; Goniocolletes dasypus sp.n.; Goniocolletes parvus sp.n.; Goniocolletes rugosus sp.n.) and 13 new species of Leioproctus (Leioproctus (Minycolletes) aquilus sp.n.; Leioproctus (Leioproctus) crinitus sp.n.; Leioproctus (Minycolletes) eruditus sp.n.; Leioproctus (Minycolletes) exiguus sp.n.; Leioproctus (Charicolletes) exleyae sp.n.; Leioproctus (Minycolletes) insitus sp.n.; Leioproctus (Leioproctus) litotes sp.n.; Leioproctus (Minycolletes) paulus sp.n.; Leioproctus (Minycolletes) pygmaeus sp.n.; Leioproctus (Leioproctus) quadrimaculatus sp.n.; Leioproctus (Fragocolletes) rutiliventris sp.n.; Leioproctus (Charicolletes) saltus sp.n., and Leioproctus (Alokocolletes) sequax sp.n.) are described. Additionally seven new species-level synonymies are recognized in Goniocolletes and 59 new species-level synonymies in Leioproctus. Most of the species in Leioproctus (Leioproctus) are placed in species groups. One species of Leioproctus with three submarginal cells was not assigned to any subgenus and is therefore treated as incertae sedis regarding its subgeneric placement: Leioproctus opaculus (Cockerell 1929). Additionally some notes on the biology of Leioproctus are provided. Leioproctus in Australia, as recognised in this paper, has 172 species.